Isolation and study of different isolates of Cucumber mosaic virus on Wild Tobacco {Nicotiana glauca Graham) in the western cost-belt of Libya - Ejmal, Mahjob A.; EL-Sanousi, Omar M.; EL-Ammari, Salah S. (Al-Mukhtar Journal of Sciences, 2009)
Using DAS-ELISA, Cucumber mosaic virus (CMV) was identified as the main virus causing mosaic symptoms on Nicotiana glauca Graham in 25 samples from five areas (Sirte, Misurata, El- Khoms- Tripoli- El-Zawia) in Libya. The CMV was found singly in some of the tested samples and with another Tobamovirus in most of them. The study included the host range of five isolates from different regions on 33 plant species or cultivars which shows different response with these isolates. Results showed that the thermal inactivation point (TIP) was between 50٥C-53٥C; dilution end point (DEP) was between 10"2 - 10"J and Longevity in vitro (LIV) was between 1/2 - 1 day. Antiserum was prepared to Misurata isolate, using this antiserum in indirect ELISA revealed that all isolates positively reacted with Misurata isolate antiserum as well as to the antiserum of Cucumber mosaic virus produced by Bio-Rad company .